PENGARUH EDUKASI MELALUI MEDIA FLIPBOOK TERHADAP PENGETAHUAN WANITA USIA SUBUR MENGENAI PERENCANAAN KEHAMILAN (Jurnal Kesehatan Siliwangi, 2023)
Background: . Good pregnancy planning can reduce the incidence of maternal mortality (MMR). The maternal mortality ratio in Cianjur Regency in 2021 is 116 per 100,000 live births. This number shows an increase compared to 2020 of 57 per 100,000 live births. Among them were found in RW 18 Kelurahan Muka with a ratio of 64 per 100,000 live births in 2022.. Objective: To determine the effect of education through flipbook on the knowledge of women of childbearing age regarding pregnancy planning. Methods: This study used a quasi-experimental design with a one-group pretest-posttest design without a control group or comparison to a sample of 76 women of childbearing age in the population 315. Knowledge data was collected using a questionnaire and analyzed using the Wilcoxon signed test to prove the research hypothesis. Results: The average score of respondents' knowledge before being given flipbook was 56.57 and the average knowledge score of respondents after being given flipbook was 83.44. The percentage increase in knowledge is 26.87, the p value on the knowledge of respondents before and after being given flipbook (p = 0.001). Conclusion: There was a significant increase in knowledge after being given education through flipbook on the knowledge of women of childbearing age regarding pregnancy planning